Different spectra of recurrent gene mutations in subsets of chronic lymphocytic leukemia harboring stereotyped B-cell receptors - Sutton, Lesley-Ann; Young, Emma; Baliakas, Panagiotis; Hadzidimitriou, Anastasia; Moysiadis, Theodoros; Plevova, Karla; Rossi, Davide; Kminkova, Jana; Stalika, Evangelia; Pedersen, Lone Bredo; Malcikova, Jitka; Agathangelidis, Andreas; et al. (Haematologica, 2016)
We report on markedly different frequencies of genetic lesions within subsets of chronic lymphocytic leukemia patients carrying mutated or unmutated stereotyped B-cell receptor immunoglobulins in the largest cohort (n=565) studied for this purpose. By combining data on recurrent gene mutations (BIRC3, MYD88, NOTCH1, SF3B1 and TP53) and cytogenetic aberrations, we reveal a subset-biased acquisition of gene mutations. More specifically, the frequency of NOTCH1 mutations was found to be enriched in subsets expressing unmutated immunoglobulin genes, i.e. #1, #6, #8 and #59 (22-34%), often in association with trisomy 12, and was significantly different (P<0.001) to the frequency observed in subset #2 (4%, aggressive disease, variable somatic hypermutation status) and subset #4 (1%, indolent disease, mutated immunoglobulin genes). Interestingly, subsets harboring a high frequency of NOTCH1 mutations were found to carry few (if any) SF3B1 mutations. This starkly contrasts with subsets #2 and #3 where, despite their immunogenetic differences, SF3B1 mutations occurred in 45% and 46% of cases, respectively. In addition, mutations within TP53, whilst enriched in subset #1 (16%), were rare in subsets #2 and #8 (both 2%), despite all being clinically aggressive. All subsets were negative for MYD88 mutations, whereas BIRC3 mutations were infrequent. Collectively, this striking bias and skewed distribution of mutations and cytogenetic aberrations within specific chronic lymphocytic leukemia subsets implies that the mechanisms underlying clinical aggressiveness are not uniform, but rather support the existence of distinct genetic pathways of clonal evolution governed by a particular stereotyped B-cell receptor selecting a certain molecular lesion(s).
Keywords: mutace; hypervariabilní oblasti; imunoglobuliny - vazebný region; Complementarity Determining Regions; Female; Immunoglobulin Variable Region; Immunoglobulin Heavy Chains; ženské pohlaví; jednonukleotidový polymorfismus; genová přestavba B-lymfocytů; cytogenetické vyšetření; Leukemia, Lymphocytic, Chronic, B-Cell; Gene Frequency; lidé; Immunoglobulin Joining Region; Polymorphism, Single Nucleotide; Cytogenetic Analysis; Mutation; těžké řetězce imunoglobulinů; frekvence genu; geny pro imunoglobuliny; prognóza; Receptors, Antigen, B-Cell; Humans; Male; nádorové biomarkery; Gene Rearrangement, B-Lymphocyte; Prognosis; receptory antigenů B-buněk; Biomarkers, Tumor; mužské pohlaví; Genes, Immunoglobulin; chronická lymfatická leukemie; variabilní oblast imunoglobulinu